The Concept and Models of the Cryptocurrency Market - AleÑ…androvich Galanov, Vladimir; Grigorevich Perepelitsa, Denis; Vladimirovna Galanova, AleÑ…andra; Fedorovna Chelukhina, Natalia; Ahmetshaevna Asyeva, Elmira (International Journal of Engineering and Technology, 2018)
In recent years, there has been an intensive market formation process which involves interrelations of various cryptocurrencies and other financial tools formed on the basis of cryptoplatforms. This process is fraught with numerous difficulties relating to determining the status of these new tools in the legal sphere of relations among market participants. However, the key role consists in the identification of the economic content of cryptotools. The purpose of the present article is to substantiate the proposals on the economic essence of cryptotools and the resulting models of their market formation. The article deals with the economic aspects of cryptotools and suggests possible models of their markets. Currently, in cryptocurrency market formation, the evolutionary path is dominated. Therefore, the article discusses the main tendencies characteristic of this development path. However, the authors also emanate from the necessity of cryptocurrency market formation under the regulating influence of the state and give recommendations on the cryptocurrency market formation based on the interaction of market participants with regulating bodies of state power. It is this approach that allows minimizing financial risks for investors, providing stability of money circulation and macroeconomic resilience, creating favorable conditions for this market to take the proper place in the contemporary economy, and in the digitalization processes occurring in the economy.Â